Reading Acquisition, Development Dylexia, and Skilled Reading Across Languages A Psycholinguistic Grain Size Theory . [article]. - Ziegler, Jhannes C.
The development of reading depends on phenological awareness across all languages so far studied. Languages vary in the consistency with which phonology is represented in orthography. This results in developmental differences in the grain size of lexical representation and accompanying differences in developmental reading strategies and manifestition of dyslexia across orthographis. Differences in lexical representations and reading across languages leave developmental "footprints" in the adult lexicon. The lexical organization and processing strategies that are characteristic of skilled reading in different orthographies are affect different developmental constraints in different writing systems. The authors develop a novel theoretical framework to explain these cross-language data, which they label a psycholinguistic grain size theory of reading and its development. [ from the authors].